Teaching experience, professional preparation, and problems encountered by special education teachers in selected public schools in Quezon City - Lai, Yi-Chich (Candy) (Animo Repository, 2005)
This study focused on determining the problems that special education teachers encounter in their work and whether or not the perceived frequency of the problems are a function of teaching experience, professional preparation, and in-service training. Specifically, this study sought answers to these questions: 1) What are the problems that special education teachers most commonly encounter in source areas such as school administration; teachers’ knowledge and skills; the students; and instructional materials and other resources; and the parents; 2) Is the perceived frequency of the occurrence of the problems related to their teaching experience and professional preparation, academic degree, and in-service training? To provide answers to the aforecited research problems, a survey questionnaire was constructed and administered to 34 participants from different special education centers in the Schools Division of Quezon City. The data gathered from these teachers showed that the most often encountered problems of special education teachers are sourced from their school administrators consisted of liaising with support services for student development, being open to suggestions and criticisms, and monitoring progress of student program implementation. Regarding teachers’ knowledge and skills as a source of problems, the most often encountered ones involved knowledge and skills in conferring with parents, maintaining order and discipline, vi and adjusting to student time and speed. With the SPED teachers’ most often encountered problems were those of the students having varied needs, ability levels, and interests, and having misplaced children with disability in the class. On the other hand, the teachers’ problems on instructional materials and resources consisted of their concerns on the appropriateness of materials to student level, their multilevel use, and adequacy in meeting instructional objectives. In terms of the parents as source of problems, high expectation from teachers, teachers listed support for children with disabilities and cooperation with school staff were reported to be the most often encountered problems. There was a high negative and significant correlation between the perceived frequency of problems encountered by special education teachers and their teaching experience. A moderate negative and significant correlation between the frequency of problems encountered and the teachers’ professional preparation in terms of academic degrees obtained. In terms of in-service trainings attended, a high significant and positive relationship was revealed.